Pengaruh Persepsi Harga, Kualitas Produk, dan Citra Merek Pada Keputusan Pembelian di Kimukatsu Grand Indonesia - Wiko Aulia Ramadhan; Leonardo Indra Vitaharsa (CV Edujavare Publishing, 2024)
The objective of this study is to analyze the impact of price perceptions, product quality and brand image on purchasing decisions at Kimukatsu Grand Indonesia. This study uses primary data by collecting questionnaires. The method used is quantitative descriptive using SPSS Version 20 software and the study population consisted of all consumers who shop at Kimukatsu Grand Indonesia. The sampling approach used in this study was accidental sampling with a sample size of 100 respondents. The data analysis used in this study is multiple linear regression analysis. The results of this study demonstrate that price perceptions partly have a positive and significant impact on purchasing decisions. In part, quality does not have a significant impact on purchasing decisions. In part, brand image does not have a significant impact on purchasing decisions. At the same time, the perception of price, product quality and brand image have a significant impact on purchasing decisions.